Spa service distribution and specialisation in kujawsko-pomorskie, pomorskie and podkarpackie voivodship communes - Stelmach, Paweł (Turyzm/Tourism, 2017)
The objective of the article is to identify and explain the relationship between spa services distribution and spa specialization in Kujawsko-Pomorskie, Pomorskie and Podkarpackie Voivodeships spa communes. Correlation and regression analysis were used based on data from the Local Data Bank and unpublished data sets from the Central Statistical Office of Poland. In order to explain the relation between spa services distribution and spa specialization, time-series analysis was used. In five of nine researched communes (Horyniec-Zdrój, Solina, Ustka, Ciechocinek and Inowrocław) there is a functional relationship between spa services distribution and spa specialization.